2014
DOI: 10.1364/boe.5.000932
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high power supercontinuum source in the 17 μm wavelength region for highly penetrative ultrahigh-resolution optical coherence tomography

Abstract: Abstract:We developed a high power supercontinuum source at a center wavelength of 1.7 μm to demonstrate highly penetrative ultrahighresolution optical coherence tomography (UHR-OCT). A single-wall carbon nanotube dispersed in polyimide film was used as a transparent saturable absorber in the cavity configuration and a high-repetition-rate ultrashort-pulse fiber laser was realized. The developed SC source had an output power of 60 mW, a bandwidth of 242 nm full-width at half maximum, and a repetition rate of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…This result indicates that the resolving power of the 1700-nm OCM in the lateral direction was close to the theoretical limit. From these experiments, we confirmed that the 1700-nm OCM provides the highest 3D spatial resolution among 1700-nm OCT imaging techniques323435363738.…”
Section: Resultssupporting
confidence: 66%
“…This result indicates that the resolving power of the 1700-nm OCM in the lateral direction was close to the theoretical limit. From these experiments, we confirmed that the 1700-nm OCM provides the highest 3D spatial resolution among 1700-nm OCT imaging techniques323435363738.…”
Section: Resultssupporting
confidence: 66%
“…There have been very few developments of long wavelength OCT beyond 1.5 μm [7][8][9][10][11][12]. We have previously demonstrated through a time-domain OCT system the significantly improved probing depth of long wavelength OCT in comparison to short wavelength sources [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…An ultrashort-pulse SWNT fiber laser is a practical laser source that is already playing a role as a useful pulse source in optical frequency combs, ultrahigh resolution optical coherence tomography, and nonlinear microscopy [22][23][24]. Especially, the performance of an optical frequency comb depends on the characteristics of the laser [25][26][27].…”
Section: Open Accessmentioning
confidence: 99%